Associated Factors and Prevention of Upper Pole Rippling in Prepectoral Direct-to-Implant Breast Reconstruction - Ryu, Da Hye; Joo, Oh Young; Roh, Yun Ho; Yang, Eun Jung; Song, Seung Yong; Lee, Dong Won (Archives of Plastic Surgery, 2023)
Background Despite its many advantages, prepectoral breast reconstruction also carries the risk of implant rippling. The recent introduction of partial superior implant coverage using a pectoralis muscle slip in prepectoral direct-to-implant (DTI) breast reconstruction has shown the potential to minimize upper pole rippling. The purpose of this study was to identify factors associated with rippling and the effectiveness of our surgical technique.Methods In total, 156 patients (186 breasts) who underwent prepectoral DTI breast reconstruction between August 2019 and March 2021 were identified retrospectively. Patient data were analyzed from medical records. Univariable and multivariable logistic analyses were performed to contextualize the risks associated with rippling deformity relative to demographic characteristics and other clinical factors. Retrospective propensity-matched analysis was performed to identify the relationship between rippling deformity and the reconstruction method.Results Patients with body mass index (BMI; odds ratio [OR], 0.736; p < 0.001), those with a postoperative chemotherapy history (OR, 0.324; p = 0.027) and those who received breast reconstruction via the superior coverage technique (OR, 0.2; p = 0.004), were less likely to develop rippling deformity. The median follow-up period was 64.9 weeks, and there were no significant differences between patients in types of mastectomy, implant, or acellular dermal matrix. Patients who underwent superior coverage technique-based reconstruction showed significantly reduced rippling (OR, 0.083; p = 0.017)Conclusion Patients with higher BMI and prior postoperative chemotherapy were less likely to develop rippling deformity. The superior coverage technique can be effective in minimizing upper pole rippling.
Keywords: breast reconstruction; prepectoral breast reconstruction; implant rippling; rippling